PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SHAMPO MEREK REJOICE PADA MASYARAKAT RANTAUPRAPAT - Elvina Elvina (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2014)
The purpose of this research is: 1) to know the influence of the price of the consumer purchasing decisions on shampoo products registered Rejoice on the community Rantauprapat, 2) to know the influence of product quality to the consumer purchasing decisions on shampoo products registered Rejoice on the community Rantauprapat. The hypothesis of this research are influential price variable significant for consumer purchasing decisions on shampoo products registered Rejoice on the community Rantauprapat, and product quality variables affect significant for consumer purchasing decisions on shampoo products registered Rejoice on the community Rantauprapat. The population of this research is the people who make purchases on the shampoo products registered Rejoice, samples in this research is 98 respondents. The results of the study showed that: 1) The prices have positive and significant impact on the consumer purchasing decisions on shampoo products registered Rejoice on the community Rantauprapat, and product quality have positive and significant impact on the consumer purchasing decisions on shampoo products registered Rejoice on the community Rantauprapat.